The role of HSP 70 in the implementation of neuroprotective effect of selective estrogen receptor modulator (SERM) in deprivation of the system`s level of restored glutathione in vitro - Korostina, K. I.; Kapitanchuk, D. S.; Коростіна, Крістіна Ігорівна (Запорізький державний медичний університет, 2022)
The aim of the research: to determine the value of the heat shock protein HSP 70 in the implementation of the mechanism of neuroprotective actions of selective estrogen receptor modulator (SERM) – (Z)-2-[4-(1,2-diphenyl-1-butenil)fenoxy]-N,N-dimethilaethanamin citrate.
Keywords: тези доповідей